Annual Report 1986-87 - Planning Commission (Planning Commission Government of India, 1986)
The Annual Report 1986-87 of the Planning Commission of India provides a detailed overview of the Commission's initiatives, achievements, and challenges during the fiscal year. Under Prime Minister Rajiv Gandhi’s leadership, the report highlights parliamentary engagements, formulation of the Annual Plan 1986-87 and 1987-88, and a focus on anti-poverty initiatives, infrastructure, and sectoral development. Key studies addressed agriculture, energy, environment, social welfare, and education, while divisions monitored and implemented programs across critical sectors. The Programme Evaluation Organisation assessed developmental programs to enhance efficiency and outcomes. The report also emphasizes international collaboration through delegations and participation in global seminars to strengthen policy-making. Overall, the document reflects the Commission’s strategic approach to sustainable, evidence-based, and inclusive socio-economic planning in India.
Government of India Planning Commission
Keywords: Planning Commission; Annual Plan; Programme Evaluation Organisation; Agriculture; Rural Development; Health; Education; Infrastructure; Economic Planning; International Collaboration